Pre-lithiated negative pole piece, lithium supplementing method, preparation method of secondary battery, secondary battery and electronic device
By using prelithiation treatment in the negative electrode sheet of lithium-ion battery, and using materials such as lithium salts, solvents and polymers to form a gel electrolyte layer and a lithium supplement layer, the problems of energy density and cycle life of the negative electrode materials of existing lithium-ion battery are solved, and higher energy density and lower cycle attenuation are achieved.
Patent Information
- Application Number
- CN202510111744.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The energy density of the existing lithium-ion battery negative electrode material graphite cannot meet the demand, and the first Coulombic efficiency of silicon carbon and silicon oxygen materials is low and the cycle life is poor, resulting in it not being widely promoted.
Using a prelithiated negative electrode sheet, a negative electrode gel mixture is formed by mixing the first lithium salt, the first solvent, the first polymer, the negative electrode active material and the negative electrode conductive agent, and applied to the surface of the negative electrode current collector to form a negative electrode material layer. Then, the second lithium salt, the second solvent and the second polymer are mixed to form the first gel electrolyte and coated on the surface of the negative electrode material layer. By bonding with the lithium supplement layer, a prelithization treatment is realized to form a prelithized negative electrode sheet.
It improves the first Coulomb efficiency of lithium-ion batteries, reduces the cycle capacity attenuation, improves the battery's energy density, and has good safety performance.
Smart Images

Figure CN119920843A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a pre-lithiated negative electrode plate, a lithium replenishment method, a secondary battery preparation method, a secondary battery and an electronic device. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, high power, and long cycle life. They are widely used in consumer electronics, electric bicycles, and electric vehicles. As their application scope continues to expand, the energy density and cycle performance requirements of lithium-ion batteries continue to increase. The current common lithium-ion battery negative electrode graphite materials can no longer meet the requirements for energy density. Although silicon-carbon and silicon-oxygen negative electrode materials have high theoretical specific capacity and are ideal materials for replacing negative electrode graphite materials and improving the energy density of lithium-ion batteries, they have not been widely used due to their low first coulomb efficiency and poor cycle life. The existing method to improve the first coulomb efficiency and reduce cycle attenuation of silicon-carbon or silicon-oxygen negative electrodes is to pre-replenish lithium to the negative electrode plate to supplement the irreversible capacity consumed during the first charge, discharge, and cycle, improve the first coulomb efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrodes, and then improve the energy density of lithium-ion batteries.
[0003] The existing negative electrode plate lithium replenishment methods mainly include lithium powder replenishment, lithium strip replenishment and electrochemical replenishment. However, the above three lithium replenishment methods have certain problems in environmental control, lithium replenishment uniformity, and side reactions after lithium replenishment. Therefore, it is urgent to provide a pre-lithiated negative electrode plate that can improve the first coulomb efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrodes, reduce cycle capacity attenuation, and improve the energy density of lithium-ion batteries. Summary of the invention
[0004] The purpose of this application is to provide a pre-lithiated negative electrode plate, a lithium replenishment method, a secondary battery preparation method, a secondary battery and an electronic device to improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery, and the secondary battery also has good safety performance. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a lithium supplementation method, which comprises the following steps:
[0006] (1) mixing a first lithium salt, a first solvent, a first polymer, a negative electrode active material, and a negative electrode conductive agent to obtain a negative electrode gel mixture;
[0007] (2) coating the negative electrode gel mixture on at least one surface of the negative electrode current collector to form a negative electrode material layer to obtain a negative electrode sheet;
[0008] (3) mixing a second lithium salt, a second solvent, and a second polymer to obtain a first gel electrolyte; coating the first gel electrolyte on the surface of the negative electrode material layer to form a first gel electrolyte layer;
[0009] (4) coating a lithium metal powder slurry on the support layer, drying it, and rolling it to form a lithium supplement layer; or rolling a lithium foil and / or a lithium alloy foil onto the support layer to form a lithium supplement layer; or coating a lithium or lithium alloy molten slurry on the support layer, cooling it, and rolling it to form a lithium supplement layer; wherein the rolling pressure P1 is 0.1T / 10mm to 2T / 10mm;
[0010] (5) The lithium supplement layer obtained in step (4) and the first gel electrolyte layer obtained in step (3) are laminated to perform a pre-lithiation treatment, wherein the lamination pressure P2 of the lithium supplement layer and the first gel electrolyte layer is 0.1 MPa to 0.6 MPa, the lamination time t2 of the lithium supplement layer and the first gel electrolyte layer is 0.01 h to 1 h, and the lamination temperature T2 of the lithium supplement layer and the first gel electrolyte layer is 25° C. to 90° C. After the pre-lithiation treatment is completed, the lithium supplement layer and the first gel electrolyte layer are peeled off to form a pre-lithiation negative electrode sheet.
[0011] The first solvent and the second solvent are each independently selected from at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, N,N-dimethylformamide, N-methylpyrrolidone, dioxolane, 1-butyl-3-methylimidazolium bromide or ethylene glycol dimethyl ether. The first polymer and the second polymer are each independently selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer or polyethylene glycol dimethacrylate.
[0012] By using the above-mentioned lithium replenishment method and applying the pre-lithiated negative electrode plate to the secondary battery, the initial coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, the energy density of the secondary battery can be improved, and the secondary battery also has good safety performance.
[0013] In one embodiment of the present application, the first lithium salt and the second lithium salt are each independently selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate) or lithium oxalatodifluoroborate. The selection of the first lithium salt and the second lithium salt can further improve the initial coulombic efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0014] In one embodiment of the present application, the concentration CLi2 of the second lithium salt in the first gel electrolyte is 0.2 mol / L to 2 mol / L; based on the mass of the first gel electrolyte layer, the mass percentage content Wp2 of the second polymer is 1% to 30%. By regulating the concentration of the second lithium salt in the first gel electrolyte and the mass percentage content of the second polymer within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the energy density of the secondary battery can be further improved.
[0015] In one embodiment of the present application, the viscosity η1 of the first gel electrolyte is 30000 mPa·s to 200000 mPa·s. By regulating the viscosity of the first gel electrolyte within the above range, the first gel electrolyte has a suitable viscosity, which is conducive to coating the first gel electrolyte on the surface of the negative electrode material layer to form a first gel electrolyte layer with suitable thickness and relatively uniform.
[0016] The second aspect of the present application provides a pre-lithiated negative electrode sheet prepared according to the lithium replenishment method in any of the aforementioned embodiments, which includes a negative electrode current collector, a negative electrode material layer and a first gel electrolyte layer, the negative electrode material layer is arranged between the negative electrode current collector and the first gel electrolyte layer, the negative electrode material layer includes a negative electrode active material, a negative electrode conductive agent, a first lithium salt, a first solvent and a first polymer, and the first gel electrolyte layer includes a second lithium salt, a second solvent and a second polymer. The pre-lithiated negative electrode sheet is applied to a secondary battery, which can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery, and the secondary battery also has good safety performance.
[0017] In one embodiment of the present application, the ionic conductivity σ of the first gel electrolyte layer is 0.1 mS / cm to 15 mS / cm. By regulating the ionic conductivity of the first gel electrolyte layer within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the energy density of the secondary battery can be further improved.
[0018] In one embodiment of the present application, the surface density CW1 of the first gel electrolyte layer is 1 g / m 2 Up to 100g / m 2 By adjusting the surface density of the first gel electrolyte layer within the above range, the initial coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the energy density of the secondary battery can be further improved.
[0019] In one embodiment of the present application, the surface density CW1 of the first gel electrolyte layer is 5 g / m 2 Up to 50g / m 2By adjusting the surface density of the first gel electrolyte layer within the above range, the initial coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the energy density of the secondary battery can be further improved.
[0020] In one embodiment of the present application, based on the mass of the negative electrode material layer, the mass percentage content W1 of the negative electrode active material is 69% to 99%, the mass percentage content W2 of the negative electrode conductive agent is 0.18% to 5.0%, and the sum of the mass percentage content W3 of the first lithium salt, the first solvent and the first polymer is 0.7% to 15%. By regulating the sum of the mass percentage content of the negative electrode active material, the negative electrode conductive agent and the first lithium salt, the first solvent and the first polymer within the above range, a gel-state negative electrode plate can be obtained, and the gel-state negative electrode plate, the gel-state positive electrode plate and the gel-state separator can form a gel-state secondary battery, which reduces the process steps, reduces the cost of the secondary battery, and the gel-state secondary battery has good safety performance.
[0021] The third aspect of the present application provides a method for preparing a secondary battery, which comprises the following steps:
[0022] (1) mixing a third lithium salt, a third solvent, a third polymer, a positive electrode active material, and a positive electrode conductive agent to obtain a positive electrode gel mixture; coating the positive electrode gel mixture on at least one surface of a positive electrode current collector to form a positive electrode material layer to obtain a gel positive electrode sheet;
[0023] (2) mixing a fourth lithium salt, a fourth solvent, and a fourth polymer to obtain a second gel electrolyte; applying the second gel electrolyte to one surface of the separator to form a second gel electrolyte layer to obtain a gel separator;
[0024] (3) The gelled positive electrode sheet, the gelled separator and the pre-lithiated negative electrode sheet in any of the above embodiments are stacked in sequence, and the second gelled electrolyte layer is arranged opposite to the gelled positive electrode sheet to obtain a secondary battery.
[0025] The third solvent and the fourth solvent are each independently selected from at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, N,N-dimethylformamide, N-methylpyrrolidone, dioxolane, 1-butyl-3-methylimidazolium bromide or ethylene glycol dimethyl ether. The third polymer and the fourth polymer are each independently selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer or polyethylene glycol dimethacrylate.
[0026] The preparation method provided by the present application is used to prepare a secondary battery, which can improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity decay, and improve the energy density of the secondary battery; and the prepared secondary battery is a gel-state secondary battery, which can reduce the process steps and reduce the cost of the secondary battery. The gel-state secondary battery does not contain free electrolyte and has good safety performance.
[0027] In one embodiment of the present application, the third lithium salt and the fourth lithium salt are each independently selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate) or lithium difluoroborate oxalate. The selection of the third lithium salt and the fourth lithium salt can further improve the first coulombic efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0028] In one embodiment of the present application, based on the mass of the positive electrode material layer, the mass percentage content W4 of the positive electrode active material is 85% to 99%, the mass percentage content W5 of the positive electrode conductive agent is 0.5% to 5%, and the sum of the mass percentage content W6 of the third lithium salt, the third solvent and the third polymer is 0.5% to 10%. By regulating the sum of the mass percentage content of the positive electrode active material, the positive electrode conductive agent and the third lithium salt, the third solvent and the third polymer within the above range, the positive electrode material layer has good electron and ion conductivity, and a gel-state positive electrode plate can be obtained. The gel-state positive electrode plate, the gel-state separator and the gel-state negative electrode plate can form a gel-state secondary battery, which reduces the process steps and reduces the cost of the secondary battery. In addition, the gel-state secondary battery does not contain a free electrolyte and has good safety performance.
[0029] In one embodiment of the present application, the concentration of the fourth lithium salt in the second gel electrolyte is CLi4 0.2 mol / L to 2 mol / L; based on the mass of the second gel electrolyte layer, the mass percentage of the fourth polymer Wp4 is 1% to 30%. By regulating the concentration of the fourth lithium salt in the second gel electrolyte and the mass percentage of the fourth polymer within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the energy density of the secondary battery can be further improved.
[0030] In one embodiment of the present application, the viscosity η2 of the second gel electrolyte is 30000 mPa·s to 200000 mPa·s. By regulating the viscosity of the second gel electrolyte within the above range, the second gel electrolyte has a suitable viscosity, which is conducive to coating the second gel electrolyte on the surface of the diaphragm to form a second gel electrolyte layer with suitable thickness and relatively uniformity.
[0031] In one embodiment of the present application, the surface density CW2 of the second gel electrolyte layer is 1 g / m2 Up to 100g / m 2 By adjusting the surface density of the second gel electrolyte layer within the above range, the initial coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the energy density of the secondary battery can be further improved.
[0032] The fourth aspect of the present application provides a secondary battery, which is prepared by the preparation method in any of the above embodiments. Therefore, the secondary battery provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density, and the secondary battery also has better safety performance.
[0033] The fifth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density, and the electronic device also has better safety performance.
[0034] Beneficial effects of this application:
[0035] The present application provides a pre-lithiated negative electrode plate, a lithium supplementation method, a method for preparing a secondary battery, a secondary battery and an electronic device, wherein the pre-lithiated negative electrode plate comprises a negative electrode current collector, a negative electrode material layer and a first gel electrolyte layer, wherein the negative electrode material layer is arranged between the negative electrode current collector and the first gel electrolyte layer, wherein the negative electrode material layer comprises a negative electrode active material, a negative electrode conductive agent, a first lithium salt, a first solvent and a first polymer, and wherein the first gel electrolyte layer comprises a second lithium salt, a second solvent and a second polymer. The pre-lithiated negative electrode plate satisfies the above characteristics, can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, improve the energy density of the secondary battery, and the secondary battery also has good safety performance.
[0036] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0038] Figure 1 A schematic diagram of the structure of a negative electrode plate, a first gel electrolyte layer and a lithium supplement layer in a pre-lithiation process of an embodiment of the present application;
[0039] Figure 2A schematic diagram of the structure of a pre-lithiated negative electrode plate according to an implementation scheme of the present application. DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0041] The first aspect of the present application provides a lithium supplementation method, which comprises the following steps:
[0042] (1) uniformly mixing a first lithium salt, a first solvent, a first polymer, a negative electrode active material, and a negative electrode conductive agent to obtain a negative electrode gel mixture;
[0043] (2) coating the negative electrode gel mixture on at least one surface of the negative electrode current collector to form a negative electrode material layer to obtain a negative electrode sheet;
[0044] (3) uniformly mixing a second lithium salt, a second solvent, and a second polymer to obtain a first gel electrolyte; coating the first gel electrolyte on the surface of the negative electrode material layer to form a first gel electrolyte layer;
[0045] (4) Under the condition of ambient temperature ≤30°C and humidity ≤1.7%, a lithium metal powder slurry is applied to the support layer and dried and rolled to form a lithium supplement layer; or a lithium foil and / or a lithium alloy foil is rolled to the support layer to form a lithium supplement layer; or a lithium or lithium alloy molten slurry is applied to the support layer and cooled and rolled to form a lithium supplement layer; wherein the roller pressure P1 is 0.1T / 10mm to 2T / 10mm; specifically, the roller pressure P11 of rolling after applying the lithium metal powder slurry to the support layer is 0.1T / 10mm to 2T / 10mm; the roller pressure P12 of rolling after rolling the lithium foil and / or the lithium alloy foil to the support layer is 0.1T / 10mm to 2T / 10mm; the roller pressure P13 of rolling after applying the lithium or lithium alloy molten slurry to the support layer is 0.1T / 10mm to 2T / 10mm;
[0046] (5) Under the condition of an ambient temperature of 25° C. to 180° C. and a humidity of ≤1.7%, the lithium supplement layer obtained in step (4) and the first gel electrolyte layer obtained in step (3) are laminated to perform a pre-lithiation treatment, wherein the lamination pressure P2 of the lithium supplement layer and the first gel electrolyte layer is 0.1 MPa to 0.6 MPa, the lamination time t2 of the lithium supplement layer and the first gel electrolyte layer is 0.01 h to 1 h, and the lamination temperature T2 of the lithium supplement layer and the first gel electrolyte layer is 25° C. to 90° C. After the pre-lithiation treatment is completed, the lithium supplement layer and the first gel electrolyte layer are peeled off to form a pre-lithiation negative electrode sheet.
[0047] The first solvent and the second solvent are each independently selected from at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propylene carbonate (PC), N,N-dimethylformamide, N-methylpyrrolidone, dioxolane, 1-butyl-3-methylimidazolium bromide or ethylene glycol dimethyl ether. The first polymer and the second polymer are each independently selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer or polyethylene glycol dimethacrylate.
[0048] Exemplarily, P1 may be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P11 may be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P12 can be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P13 can be 0.1T / 10mm, 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, 2T / 10mm, or a range consisting of any two of the above values. P2 can be 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, or a range consisting of any two of the above values. t2 can be 0.01h, 0.05h, 0.1h, 0.3h, 0.5h, 0.7h, 0.9h, 1h, or a range consisting of any two of the above values. T2 can be 25°C, 40°C, 50°C, 60°C, 80°C, 90°C, or a range consisting of any two of the above values.
[0049] In the present application, in the above step (1), specifically, the first lithium salt, the first solvent, and the first polymer can be mixed evenly to obtain a first intermediate, and then the negative electrode active material and the negative electrode conductive agent are added and mixed evenly to obtain a negative electrode gel mixture. Based on the mass of the negative electrode gel mixture, the mass percentage w1 of the negative electrode active material is 80% to 99%, the mass percentage w2 of the negative electrode conductive agent is 0.2% to 5%, and the sum of the mass percentages w3 of the first lithium salt, the first solvent and the first polymer is 0.8% to 15%. The concentration CLi1 of the first lithium salt in the first intermediate is 0.2mol / L to 2mol / L; based on the mass of the first intermediate, the mass percentage Wp1 of the first polymer is 1% to 30%. The negative electrode active material may include at least one of a graphite material, hard carbon, a silicon-carbon material or a silicon-oxygen material. The above-mentioned graphite material includes at least one of artificial graphite or natural graphite. The silicon-carbon material is a silicon-carbon composite material, and the mass percentage of silicon element is 30% to 70% and the mass percentage of carbon element is 30% to 70% based on the mass of the silicon-carbon composite material. The present application has no special restrictions on the silicon-carbon composite material, as long as the purpose of the present application can be achieved. For example, the silicon-carbon composite material can be a composite material obtained by deposition. Exemplarily, the silicon-carbon composite material can be a silicon material deposited on a carbon skeleton, or a carbon material deposited on a silicon skeleton. The silicon-oxygen material includes SiOx, where 0<x<2. Exemplarily, the silicon-oxygen material can include silicon oxide (SiO, the molar ratio of silicon to oxygen is 1:1). The present application has no special restrictions on the type of negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can include but is not limited to at least one of conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. The above-mentioned conductive carbon black can include but is not limited to at least one of Super P, acetylene black or Ketjen black. The above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or few-walled carbon nanotubes. The carbon fiber may include but is not limited to at least one of vapor grown carbon fiber (VGCF) or nano carbon fiber. The metal material may include but is not limited to metal powder and / or metal fiber, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.
[0050] In the above step (2), the coating method of coating the negative electrode gel mixture on the surface of the negative electrode current collector can be blade coating, extrusion coating or transfer coating. The above “coating the negative electrode gel mixture on at least one surface of the negative electrode current collector to form a negative electrode material layer” means that the negative electrode material layer can be arranged on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the “surface” here can be the entire area of the negative electrode current collector, or it can be a partial area of the negative electrode current collector. This application is not particularly limited, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved, for example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper or composite current collector (such as lithium copper composite current collector, carbon copper composite current collector, nickel copper composite current collector, titanium copper composite current collector, etc.). This application has no special restrictions on the thickness of the negative electrode current collector, as long as the purpose of this application can be achieved, for example, the thickness of the negative electrode current collector is 4μm to 20μm. The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30 μm to 250 μm. The present application has no particular limitation on the surface density of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the surface density of the negative electrode material layer is 2.0 g / m 2 Up to 47.5g / m 2 It can be understood that the negative electrode sheet obtained in step (2) is a gel-state negative electrode sheet.
[0051] In the above step (3), specifically, the second polymer can be dissolved in the second solvent, and then the second lithium salt is added and mixed uniformly to obtain the first gel electrolyte. The coating method of applying the first gel electrolyte to the surface of the negative electrode material layer can be blade coating, extrusion coating or transfer coating. In the above step (4), the lithium alloy foil can include but is not limited to lithium aluminum alloy, and the lithium alloy in the lithium alloy molten slurry can include but is not limited to lithium aluminum alloy.
[0052] The present application has no particular restrictions on the manner in which the lithium-replenishing layer and the first gel electrolyte layer are bonded, as long as the purpose of the present application can be achieved. For example, the lithium-replenishing layer and the first gel electrolyte layer can be bonded by winding into a roll or pressing into a sheet. The present application has no particular restrictions on the method for regulating the bonding pressure, as long as the purpose of the present application can be achieved. For example, when the lithium-replenishing layer and the negative electrode sheet are wound into a roll, the bonding pressure between the lithium-replenishing layer and the first gel electrolyte layer can be regulated by regulating the winding tension. For example, when the lithium-replenishing layer and the negative electrode sheet are pressed into a sheet, the bonding pressure between the lithium-replenishing layer and the first gel electrolyte layer can be regulated by regulating the pressing pressure.
[0053] The inventors have found that the negative electrode material layer includes a first lithium salt, a first solvent and a first polymer, and the negative electrode material layer is in a gel state. Then, a second lithium salt, a second solvent and a second polymer are evenly mixed, and the types of the second solvent and the second polymer are within the scope of the present application, to obtain a first gel electrolyte, and the first gel electrolyte is coated on the surface of the negative electrode material layer to form a first gel electrolyte layer; the first gel electrolyte layer has a suitable ion conductivity, and the lithium supplement layer is in contact with the first gel electrolyte layer, such as Figure 1 As shown, negative electrode material layers 15 are provided on two surfaces of the negative electrode current collector 14 along its thickness direction. It can be understood that the above-mentioned "negative electrode material layer 15" refers to the negative electrode material layer of the negative electrode plate that has not been pre-lithiated. The first gel electrolyte layer 13 is provided on the surface of the negative electrode material layer 15 away from the negative electrode current collector 14. The lithium supplement layer 12 is provided between the support layer 11 and the first gel electrolyte layer 13, and the lithium supplement layer 12 is in contact with the first gel electrolyte layer 13. The lithium supplement layer 12 and the negative electrode material layer 15 are electrochemically short-circuited through the first gel electrolyte layer 13. The lithium atoms in the lithium supplement layer undergo an oxidation reaction to lose electrons to generate lithium ions. The electrons and lithium ions are transferred to the surface or the inside of the negative electrode material layer through the first gel electrolyte layer. The electrons and lithium ions undergo a reduction reaction in the negative electrode material layer to form a lithium intercalation compound, thereby realizing the pre-lithiation process of the negative electrode material layer. In the above-mentioned pre-lithiation process, the amount of lithium replenishment can be controlled by controlling the laminating pressure, laminating time, and laminating temperature, and rapid lithium replenishment can be achieved at the same time, and the possibility of introducing impurities into the lithium replenishment layer can be reduced, which is beneficial to improving the initial coulomb efficiency of the secondary battery, reducing the cycle capacity decay, and improving the energy density of the secondary battery. The lithium replenishment layer with the support layer is peeled off from the first gel electrolyte layer to obtain a pre-lithiation negative electrode plate, and the pre-lithiation negative electrode plate includes a negative electrode material layer and a first gel electrolyte layer. The above-mentioned pre-lithiation negative electrode plate, gel positive electrode plate, and gel separator can form a gel secondary battery, which reduces the process steps and reduces the cost of the secondary battery. In addition, the gel secondary battery does not contain free electrolyte and has good safety performance.
[0054] In one embodiment of the present application, the first lithium salt and the second lithium salt are independently selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(oxalatoborate) or lithium oxalatodifluoroborate. The first lithium salt is selected so that the negative electrode material layer has a suitable ionic conductivity; the second lithium salt is selected so that the first gel electrolyte layer has a suitable ionic conductivity, so that electrons and lithium ions can be transferred to the surface or the inside of the negative electrode material layer more quickly through the first gel electrolyte layer, so that lithium can be replenished more quickly and the amount of lithium replenished can be further increased, thereby further improving the initial coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.
[0055] In one embodiment of the present application, the concentration CLi2 of the second lithium salt in the first gel electrolyte is 0.2 mol / L to 2 mol / L; based on the mass of the first gel electrolyte layer, the mass percentage content Wp2 of the second polymer is 1% to 30%. Exemplarily, the value of CLi2 can be 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2 or a range consisting of any two of the above values; the value of Wp2 can be 1%, 5%, 8%, 10%, 15%, 18%, 20%, 25%, 28%, 30% or a range consisting of any two of the above values. The concentration of the second lithium salt in the first gel electrolyte will affect the ionic conductivity of the first gel electrolyte layer, and thus affect the lithium replenishment rate and amount. By regulating the concentration of the second lithium salt in the first gel electrolyte and the mass percentage of the second polymer within the above range, it is beneficial to obtain an electrolyte system with excellent mechanical properties, high ionic conductivity and good compatibility, so that the first gel electrolyte layer can have a suitable ionic conductivity, and electrons and lithium ions can be more quickly transferred to the surface or inside of the negative electrode material layer through the first gel electrolyte layer, so as to achieve the effect of rapid lithium replenishment and increase the amount of lithium replenishment, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery. The present application has no particular restrictions on the method of regulating the concentration of the second lithium salt in the first gel electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the second lithium salt can be regulated by regulating the amount of the second lithium salt added. Exemplarily, the amount of the second lithium salt added increases, and the concentration of the second lithium salt increases; the amount of the second lithium salt added decreases, and the concentration of the second lithium salt decreases. The present application has no particular restrictions on the method of regulating the mass percentage of the second polymer, as long as the purpose of the present application can be achieved. For example, the mass percentage of the second polymer can be regulated by regulating the amount of the second polymer added.
[0056] In one embodiment of the present application, the viscosity η1 of the first gel electrolyte is 30000 mPa·s to 200000 mPa·s. Exemplarily, the value of η1 can be 30000, 50000, 70000, 90000, 100000, 130000, 150000, 170000, 190000, 200000 or a range consisting of any two of the above values. By regulating the viscosity of the first gel electrolyte within the above range, the first gel electrolyte has a suitable viscosity, which is conducive to coating the first gel electrolyte on the surface of the negative electrode material layer to form a first gel electrolyte layer with suitable thickness and relatively uniform.
[0057] In one embodiment of the present application, the first solvent includes ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate. Based on the total volume of the first solvent, the volume percentage of ethylene carbonate is 20% to 50%, the volume percentage of dimethyl carbonate is 20% to 50%, the volume percentage of ethyl methyl carbonate is 0% to 30%, and the volume percentage of diethyl carbonate is 0% to 30%.
[0058] In one embodiment of the present application, the second solvent includes ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate. Based on the total volume of the second solvent, the volume percentage of ethylene carbonate is 20% to 50%, the volume percentage of dimethyl carbonate is 20% to 50%, the volume percentage of ethyl methyl carbonate is 0% to 30%, and the volume percentage of diethyl carbonate is 0% to 30%.
[0059] In one embodiment of the present application, the thickness H1 of the first gel electrolyte layer is 0.5 μm to 50 μm, preferably, the thickness H1 of the first gel electrolyte layer is 1 μm to 20 μm. Exemplarily, the value of H1 can be 0.5, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range consisting of any two of the above values. By regulating the thickness of the first gel electrolyte layer within the scope of the present application, the first gel electrolyte layer has a suitable thickness, the transmission distance of electrons and lithium ions is moderate, and the electrons and lithium ions can effectively recombine to form lithium-inserted compounds, which is beneficial to improve the lithium replenishment rate and amount, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.
[0060] In one embodiment of the present application, the thickness H2 of the lithium replenishment layer is 0.001mm to 1mm, and preferably, the thickness of the lithium replenishment layer is 0.005mm to 0.1mm. Exemplarily, the value of H2 can be 0.001, 0.003, 0.005, 0.007, 0.009, 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.3, 0.5, 0.7, 0.9, 1 or a range consisting of any two of the above values. By regulating the thickness of the lithium replenishment layer within the scope of the present application, the lithium replenishment layer has a suitable thickness, and the lithium replenishment layer can provide a suitable number of lithium atoms, which is beneficial to increase the amount of lithium replenishment in the negative electrode material layer, and can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0061] In one embodiment of the present application, along the running direction of the lithium replenishing layer, that is, the MD direction, the tensile strength K1 of the lithium replenishing layer (including the supporting layer) is 0.5N / 10mm to 200N / 10mm. Preferably, the tensile strength K1 of the lithium replenishing layer (including the supporting layer) is 1N / 10mm to 100N / 10mm. Along the running direction of the lithium replenishing layer, the tensile strength of the lithium replenishing layer is within the scope of the present application. The lithium replenishing layer has a high mechanical strength, which can better meet the need of peeling the lithium replenishing layer from the surface of the first gel electrolyte layer after lithium replenishment, which is conducive to further replenishing lithium to the negative electrode plate, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.
[0062] In one embodiment of the present application, the thickness H3 of the support layer is 3 μm to 50 μm, preferably, the thickness H3 of the support layer is 5 μm to 20 μm. By adjusting the thickness of the support layer within the scope of the present application, it is possible to provide better support for the lithium replenishment layer, improve the mechanical strength, better meet the need of the lithium replenishment layer to be peeled off from the surface of the first gel electrolyte layer after lithium replenishment, and facilitate further lithium replenishment of the negative electrode sheet, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.
[0063] In one embodiment of the present application, the support layer includes at least one of metal foil, polyethylene terephthalate film, polypropylene film, polyethylene film or polyimide film, and the metal foil includes copper foil, nickel foil, steel foil or copper-nickel alloy foil. By selecting the above support layer, better support can be provided for the lithium replenishing layer, so that the lithium replenishing layer can be more smoothly peeled off from the surface of the first gel electrolyte layer after lithium replenishment, which is conducive to further replenishing lithium to the negative electrode plate, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.
[0064] The second aspect of the present application provides a pre-lithiated negative electrode sheet prepared by the lithium replenishment method in any of the aforementioned embodiments, such as Figure 2 As shown, the pre-lithiation negative electrode sheet includes a negative electrode current collector 14, a negative electrode material layer 15 and a first gel electrolyte layer 13, the negative electrode material layer 15 is arranged between the negative electrode current collector 14 and the first gel electrolyte layer 13, the negative electrode material layer 15 includes a negative electrode active material, a negative electrode conductive agent, a first lithium salt, a first solvent and a first polymer, and the first gel electrolyte layer 13 includes a second lithium salt, a second solvent and a second polymer. It can be understood that after the pre-lithiation treatment, the first solvent in the negative electrode material layer of the obtained negative electrode sheet will volatilize to a certain extent.
[0065] The lithium replenishment method provided in the present application is used to prepare a pre-lithiated negative electrode plate, the pre-lithiated negative electrode plate includes a negative electrode current collector, a negative electrode material layer and a first gel electrolyte layer, the negative electrode material layer includes a negative electrode active material, a negative electrode conductive agent, a first lithium salt, a first solvent and a first polymer, the negative electrode material layer is in a gel state, and the first gel electrolyte layer includes a second lithium salt, a second solvent and a second polymer; the negative electrode material layer has a high lithium replenishment amount, and the impurities in the lithium replenishment layer introduced into the negative electrode material layer are relatively small. The pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. The negative electrode plate is a gel negative electrode plate, and the gel negative electrode plate, the gel positive electrode plate and the gel separator can form a gel secondary battery, which reduces the process steps and reduces the cost of the secondary battery. The gel secondary battery does not contain free electrolyte and has good safety performance.
[0066] In one embodiment of the present application, the ionic conductivity σ of the first gel electrolyte layer is 0.1mS / cm to 15mS / cm. Exemplarily, the value of σ can be 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or a range consisting of any two of the above values. By regulating the ionic conductivity of the first gel electrolyte layer within the above range, the first gel electrolyte layer has a suitable ionic conductivity, the ion conductivity of the first gel electrolyte layer is relatively high, the lithium replenishment layer is in contact with the first gel electrolyte layer, and the lithium replenishment layer and the negative electrode material layer are electrochemically short-circuited through the first gel electrolyte layer, which can replenish lithium more quickly and further increase the amount of lithium replenishment, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery. The present application does not particularly limit the method of regulating the ionic conductivity of the first gel electrolyte layer, as long as the purpose of the present application can be achieved. For example, the ionic conductivity of the first gel electrolyte layer can be regulated by regulating the ionic conductivity of the first gel electrolyte. Exemplarily, the ionic conductivity of the first gel electrolyte can be regulated by regulating the amount of the second lithium salt added and the degree of dissociation of the second lithium salt in the second solvent. For example, with the addition of the second lithium salt, the initial second lithium salt content is low, the degree of dissociation of the second lithium salt in the second solvent remains unchanged, and the ionic conductivity of the first gel electrolyte increases; with the increase in the amount of the second lithium salt added, the degree of dissociation of the second lithium salt in the second solvent decreases, and the ionic conductivity of the first gel electrolyte first increases and then decreases.
[0067] In one embodiment of the present application, the surface density CW1 of the first gel electrolyte layer is 1 g / m 2 Up to 100g / m 2In one embodiment of the present application, the surface density CW1 of the first gel electrolyte layer is 5 g / m 2 Up to 50g / m 2 . Exemplarily, the value of CW1 can be 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 or a range consisting of any two of the above values. By regulating the surface density of the first gel electrolyte layer within the above range, the first gel electrolyte layer can be made more continuous and the uniformity of lithium replenishment can be improved; and the lithium ion transmission distance can be moderate, which is beneficial to increase the amount of lithium ions passing through per unit time, and is beneficial to increase the lithium replenishment rate and amount, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery. The present application has no particular restrictions on the method of regulating the surface density of the first gel electrolyte layer, as long as the purpose of the present application can be achieved. For example, the surface density of the first gel electrolyte layer can be regulated by regulating the coating amount of the first gel electrolyte. Exemplarily, when the first gel electrolyte is coated on the surface of the negative electrode material layer, the coating amount of the first gel electrolyte is increased to increase the surface density of the first gel electrolyte layer; the coating amount of the first gel electrolyte is reduced to reduce the surface density of the first gel electrolyte layer.
[0068] In one embodiment of the present application, in the pre-lithiated negative electrode plate, based on the mass of the negative electrode material layer, the mass percentage W1 of the negative electrode active material is 69% to 99%, the mass percentage W2 of the negative electrode conductive agent is 0.18% to 5.0%, and the sum of the mass percentages W3 of the first lithium salt, the first solvent and the first polymer is 0.7% to 15%. Exemplarily, the value of W1 can be 69%, 70%, 73%, 75%, 77%, 79%, 80%, 81%, 83%, 85%, 87%, 89%, 90%, 91%, 93%, 95%, 97%, 99%, or a range consisting of any two of the above values; the value of W2 can be 0.18%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 4.8%, 5.0%, or a range consisting of any two of the above values; the value of W3 can be 0.7%, 0.8%, 1%, 3%, 5%, 7%, 9%, 10%, 11%, 13%, 14.4%, 15%, or a range consisting of any two of the above values. By regulating the sum of the mass percentages of the negative electrode active material, the negative electrode conductive agent, the first lithium salt, the first solvent, and the first polymer within the above range, the negative electrode material layer has good electron and ion conductivity, and a gel-state negative electrode plate can be obtained. The gel-state negative electrode plate, the gel-state positive electrode plate, and the gel-state separator can form a gel-state secondary battery, which reduces the process steps and reduces the cost of the secondary battery. In addition, the gel-state secondary battery does not contain a free electrolyte and has good safety performance. The present application has no particular restrictions on the manner of regulating the sum of the mass percentages of the negative electrode active material, the negative electrode conductive agent, the first lithium salt, the first solvent, and the first polymer, as long as the purpose of the present application can be achieved. For example, the mass percentage of the negative electrode active material can be regulated by regulating the amount of the negative electrode active material added; the mass percentage of the negative electrode conductive agent can be regulated by regulating the amount of the negative electrode conductive agent added; the sum of the mass percentages of the first lithium salt, the first solvent, and the first polymer can be regulated by regulating the amount of the first lithium salt, the first solvent, and the first polymer added. For example, when other conditions remain unchanged, the amount of lithium replenishment in the negative electrode sheet can be adjusted by adjusting the lamination pressure, lamination time, lamination temperature and other parameters in the pre-lithiation process, thereby adjusting the mass percentage of the negative electrode active material. It is understandable that in the pre-lithiation negative electrode sheet, the negative electrode material layer includes the negative electrode active material, the negative electrode conductive agent, the first lithium salt, the first solvent, the first polymer and the lithium added after the pre-lithiation.
[0069] The third aspect of the present application provides a method for preparing a secondary battery, which comprises the following steps:
[0070] (1) mixing a third lithium salt, a third solvent, a third polymer, a positive electrode active material, and a positive electrode conductive agent to obtain a positive electrode gel mixture; coating the positive electrode gel mixture on at least one surface of a positive electrode current collector to form a positive electrode material layer to obtain a gel positive electrode sheet;
[0071] (2) mixing a fourth lithium salt, a fourth solvent, and a fourth polymer to obtain a second gel electrolyte; applying the second gel electrolyte to one surface of the separator to form a second gel electrolyte layer to obtain a gel separator;
[0072] (3) The gelled positive electrode sheet, the gelled separator and the pre-lithiated negative electrode sheet in any of the above embodiments are stacked in sequence, and the second gelled electrolyte layer is arranged opposite to the gelled positive electrode sheet to obtain a secondary battery.
[0073] The third solvent and the fourth solvent are each independently selected from at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, N,N-dimethylformamide, N-methylpyrrolidone, dioxolane, 1-butyl-3-methylimidazolium bromide or ethylene glycol dimethyl ether. The third polymer and the fourth polymer are each independently selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer or polyethylene glycol dimethacrylate.
[0074] In the present application, in the above step (1), specifically, the third lithium salt, the third solvent, and the third polymer can be mixed evenly to obtain a second intermediate, and then the positive electrode active material and the positive electrode conductive agent are added and mixed evenly to obtain a positive electrode gel mixture. The concentration CLi3 of the third lithium salt in the second intermediate is 0.2 mol / L to 2 mol / L; based on the mass of the second intermediate, the mass percentage content Wp3 of the third polymer is 1% to 30%. The positive electrode active material includes a substance that can reversibly embed and extract active ions such as lithium ions. The present application has no special restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. The above-mentioned lithium nickel cobalt manganese oxide may include LiNi 0.95 Co 0.03 Mn 0.02 O2(Ni95),LiNi 0.91 Co 0.03 Mn 0.06 O2(Ni91), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523) or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 At least one of O2 (NCM111). The present application has no particular restrictions on the positive electrode conductive agent in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode conductive agent in the positive electrode material layer may include at least one of the above-mentioned negative electrode conductive agents.
[0075] The coating method of coating the positive electrode gel mixture on the surface of the positive electrode collector can be blade coating, extrusion coating or transfer coating. The above-mentioned "coating the positive electrode gel mixture on at least one surface of the positive electrode collector to form a positive electrode material layer" means that the positive electrode material layer can be arranged on one surface of the positive electrode collector along its own thickness direction, or on two surfaces of the positive electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the positive electrode collector or a partial area of the positive electrode collector. This application is not particularly limited, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode collector, as long as the purpose of this application can be achieved. For example, it can include aluminum foil, aluminum alloy foil or composite collector (such as aluminum-carbon composite collector). This application has no special restrictions on the thickness of the positive electrode collector, as long as the purpose of this application can be achieved. For example, the thickness of the positive electrode collector is 6μm to 25μm. This application has no special restrictions on the thickness of the positive electrode material layer, as long as the purpose of this application can be achieved. For example, the thickness of the single-sided positive electrode material layer is 25μm to 250μm. The present application has no particular limitation on the surface density of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the surface density of the positive electrode material layer is 4 g / m 2 Up to 95g / m 2 .
[0076] In the above step (2), specifically, the fourth polymer can be dissolved in the fourth solvent, and then the fourth lithium salt is added and mixed evenly to obtain the second gel electrolyte. The coating method of applying the second gel electrolyte to the surface of the diaphragm can be blade coating, extrusion coating or transfer coating. The "surface" in the above "coating the second gel electrolyte on a surface of the diaphragm" can be the entire area of the diaphragm or a partial area of the diaphragm. This application is not particularly limited as long as the purpose of this application can be achieved. In one embodiment of the present application, the thickness H4 of the second gel electrolyte layer is 0.5μm to 50μm, and preferably, the thickness H4 of the second gel electrolyte layer is 1μm to 20μm. This application has no special restrictions on the diaphragm as long as the purpose of this application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane. In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite membrane having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite membrane may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a diaphragm binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it can include aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. At least one of the diaphragm binder is not particularly limited in the present application, for example, the diaphragm binder can include polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene-butadiene rubber, SBR), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, lithium carboxymethyl cellulose, lithium polyacrylate, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or vinylidene fluoride-hexafluoropropylene copolymer.
[0077] In the present application, the secondary battery includes a shell for accommodating a gel-state positive electrode plate, a gel-state separator, a pre-lithiated negative electrode plate, and other components known in the field of secondary batteries. The present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, which can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal. The present application does not limit the type of metal, and a metal hard shell known in the art can be used, as long as the purpose of the present application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0078] In the above step (3), specifically, it may include but is not limited to the following steps: stacking the gel-state positive electrode sheet, the gel-state separator and the pre-lithiated negative electrode sheet in sequence, wherein the second gel-state electrolyte layer is arranged relative to the gel-state positive electrode sheet, and winding, folding and other operations are performed as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, and packaging, forming and degassing to obtain a secondary battery; or stacking the gel-state positive electrode sheet, the gel-state separator and the pre-lithiated negative electrode sheet in sequence, wherein the second gel-state electrolyte layer is arranged relative to the gel-state positive electrode sheet, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a shell, and packaging, forming and degassing to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.
[0079] A secondary battery is prepared by the preparation method provided in the present application. The secondary battery includes a gel-state positive electrode plate, a gel-state separator and a pre-lithiated negative electrode plate. The negative electrode material layer of the negative electrode plate has a high lithium supplement amount, which can improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity decay, and improve the energy density of the secondary battery; and the prepared secondary battery is a gel-state secondary battery, which can reduce the process steps and reduce the cost of the secondary battery. The gel-state secondary battery does not contain free electrolyte and has good safety performance.
[0080] In one embodiment of the present application, the third lithium salt and the fourth lithium salt are independently selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(oxalatoborate) or lithium difluoroborate oxalate. The third lithium salt is selected so that the positive electrode material layer has a suitable ionic conductivity; the fourth lithium salt is selected so that the second gel electrolyte layer has a suitable ionic conductivity, and the second gel electrolyte layer has a good ion conductivity, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the energy density of the secondary battery.
[0081] In one embodiment of the present application, based on the mass of the positive electrode material layer, the mass percentage content W4 of the positive electrode active material is 85% to 99%, the mass percentage content W5 of the positive electrode conductive agent is 0.5% to 5%, and the sum of the mass percentage content W6 of the third lithium salt, the third solvent and the third polymer is 0.5% to 10%. For example, the value of W4 can be 85%, 87%, 89%, 90%, 91%, 93%, 95%, 97%, 99% or a range consisting of any two of the above values; the value of W5 can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of the above values; the value of W6 can be 0.5%, 0.8%, 1%, 3%, 5%, 7%, 9%, 10% or a range consisting of any two of the above values. By regulating the sum of the mass percentages of the positive electrode active material, the positive electrode conductive agent, the third lithium salt, the third solvent, and the third polymer within the above range, the positive electrode material layer has good electron and ion conductivity, and a gel-state positive electrode plate can be obtained. The gel-state positive electrode plate, the gel-state separator, and the gel-state negative electrode plate can form a gel-state secondary battery, which reduces the process steps and reduces the cost of the secondary battery. In addition, the gel-state secondary battery does not contain a free electrolyte and has good safety performance. The present application has no particular restrictions on the manner of regulating the sum of the mass percentages of the positive electrode active material, the positive electrode conductive agent, the third lithium salt, the third solvent, and the third polymer, as long as the purpose of the present application can be achieved. For example, the mass percentage of the positive electrode active material can be regulated by regulating the amount of the positive electrode active material added; the mass percentage of the positive electrode conductive agent can be regulated by regulating the amount of the positive electrode conductive agent added; the sum of the mass percentages of the third lithium salt, the third solvent, and the third polymer can be regulated by regulating the amount of the third lithium salt, the third solvent, and the third polymer added.
[0082] In one embodiment of the present application, the concentration CLi4 of the fourth lithium salt in the second gel electrolyte is 0.2 mol / L to 2 mol / L; based on the mass of the second gel electrolyte layer, the mass percentage content Wp4 of the fourth polymer is 1% to 30%. Exemplarily, the value of CLi4 can be 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2 or a range consisting of any two of the above values; the value of Wp4 can be 1%, 5%, 8%, 10%, 15%, 18%, 20%, 25%, 28%, 30% or a range consisting of any two of the above values. By regulating the concentration of the fourth lithium salt in the second gel electrolyte and the mass percentage of the fourth polymer within the above range, it is beneficial to obtain an electrolyte system with excellent mechanical properties, high ionic conductivity and good compatibility, so that the second gel electrolyte layer can have a suitable ionic conductivity, and the second gel electrolyte layer has good ion conductivity, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity decay, and further improving the energy density of the secondary battery. The present application has no particular restrictions on the method of regulating the concentration of the fourth lithium salt in the second gel electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the fourth lithium salt can be regulated by regulating the amount of the fourth lithium salt added. Exemplarily, the amount of the fourth lithium salt added increases, and the concentration of the fourth lithium salt increases; the amount of the fourth lithium salt added decreases, and the concentration of the fourth lithium salt decreases. The present application has no particular restrictions on the method of regulating the mass percentage of the fourth polymer, as long as the purpose of the present application can be achieved. For example, the mass percentage of the fourth polymer can be regulated by regulating the amount of the fourth polymer added.
[0083] In one embodiment of the present application, the viscosity η2 of the second gel electrolyte is 30000 mPa·s to 200000 mPa·s. Exemplarily, the value of η2 can be 30000, 50000, 70000, 90000, 100000, 130000, 150000, 170000, 190000, 200000 or a range consisting of any two of the above values. By regulating the viscosity of the second gel electrolyte within the above range, the second gel electrolyte has a suitable viscosity, which is conducive to coating the second gel electrolyte on the surface of the diaphragm to form a second gel electrolyte layer of suitable thickness and relatively uniform.
[0084] In one embodiment of the present application, the surface density CW2 of the second gel electrolyte layer is 1 g / m 2 Up to 100g / m 2 In one embodiment of the present application, the surface density CW2 of the second gel electrolyte layer is 5 g / m 2 Up to 50g / m 2. Exemplarily, the value of CW2 can be 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 or a range consisting of any two of the above values. By regulating the surface density of the second gel electrolyte layer within the above range, the second gel electrolyte layer can be made more continuous, and the second gel electrolyte layer has a suitable thickness, which can make the lithium ion transmission distance moderate, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity decay, and further improving the energy density of the secondary battery. The present application has no particular restrictions on the method of regulating the surface density of the second gel electrolyte layer, as long as the purpose of the present application can be achieved. For example, the surface density of the second gel electrolyte layer can be regulated by regulating the coating amount of the second gel electrolyte. Exemplarily, when the second gel electrolyte is coated on the surface of the diaphragm, the coating amount of the second gel electrolyte is increased to increase the surface density of the second gel electrolyte layer; the coating amount of the second gel electrolyte is reduced to reduce the surface density of the second gel electrolyte layer.
[0085] The fourth aspect of the present application provides a secondary battery, which is prepared by the preparation method in any of the above embodiments. Therefore, the secondary battery provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density, and the secondary battery also has better safety performance.
[0086] The fifth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density, and the electronic device also has better safety performance.
[0087] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0088] Example
[0089] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0090] Test methods and equipment:
[0091] Ionic conductivity test of the first gel electrolyte layer:
[0092] (1) The first gel electrolyte was coated on the surface of the mold, and then peeled off to obtain a first gel electrolyte layer sample of 40 mm×40 mm.
[0093] (2) The first gel electrolyte layer sample is sandwiched between two platinum electrodes to ensure good contact between the first gel electrolyte layer sample and the platinum electrodes.
[0094] (3) Using an electrochemical workstation, connect the first gel electrolyte layer sample and the platinum electrode to a battery fixture, and set the electrochemical impedance spectroscopy (EIS) test parameters with a frequency range of 1 MHz to 1 Hz and an AC voltage amplitude of 5 mV.
[0095] (4) Perform EIS test at room temperature and record impedance data at different frequencies.
[0096] (5) The impedance data was fitted using the Randles equivalent circuit model, and the resistance R of the first gel electrolyte layer sample was obtained from the fitting results. b , and the ionic conductivity σ is calculated according to the following formula:
[0097] σ=L / (R b ×a); wherein, L is the thickness of the first gel electrolyte layer sample, and a is the cross-sectional area of the first gel electrolyte layer sample.
[0098] Lithium supplement test:
[0099] Use a 1 / 100,000 analytical balance to weigh the mass of the lithium supplement layer before lithium supplementation and the mass of the lithium supplement layer after lithium supplementation and after DMC cleaning and drying. The area of the lithium supplement layer is 1540.25mm 2 The ratio of the mass of the lithium replenishing layer before lithium replenishing to the area of the lithium replenishing layer is the surface density before lithium replenishing (including the surface density of the supporting layer); the ratio of the mass of the lithium replenishing layer after lithium replenishing and washing with DMC and drying to the area of the lithium replenishing layer is the surface density after lithium replenishing (including the surface density of the supporting layer); the lithium replenishment amount is the difference between the surface density before lithium replenishment and the surface density after lithium replenishment. 24 groups of lithium replenishing layers (including the supporting layer) are measured and the average value is calculated to obtain the lithium replenishment amount.
[0100] First coulombic efficiency test:
[0101] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: charge the secondary battery in the embodiment or comparative example at 25°C at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, stand for 5 minutes, and then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V. The capacity of the above charging process is recorded as C0, and the capacity of the above discharging process is recorded as C1. The first coulomb efficiency is calculated according to the following formula.
[0102] First coulombic efficiency (%) = C1 / C0×100%.
[0103] Cycle performance test:
[0104] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, the secondary battery in the embodiment or comparative example is charged and discharged for the first time, charged at a constant current of 0.2C to a cut-off voltage of 4.45V, and then charged at a constant voltage of 4.45V until the current is less than 0.05C, and after standing for 5 minutes, discharged at a constant current of 0.2C to a cut-off voltage of 3.0V, and the discharge capacity of the secondary battery is measured to be A; then, 400 charging and discharging cycles are performed according to the above steps in an environment of 25°C, and the discharge capacity of the secondary battery at the 400th time is measured to be B, and the cycle capacity retention rate is calculated according to the following formula.
[0105] Cycle capacity retention rate (%) = B / A × 100%.
[0106] The larger the value of the cycle capacity retention rate obtained from the test, the better the cycle performance of the secondary battery.
[0107] Energy density test:
[0108] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, charge the secondary battery in the embodiment or comparative example at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, let it stand for 5 minutes, then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V, and let it stand for 5 minutes. The energy of the above discharge process is recorded as the discharge energy E. Calculate the volume V (mm) of the secondary battery 3 ) = length × width × height.
[0109] Energy density (Wh / L) = E / V × 10 6 .
[0110] Example 1-1
[0111] <Preparation of pre-lithiated negative electrode sheet>
[0112] (1) The first lithium salt LiPF6, the first solvent, and the first polymer polyvinylidene fluoride are mixed evenly to obtain a first intermediate, and then the negative electrode active material silicon carbon material and the negative electrode conductive agent acetylene black are added and mixed evenly to obtain a negative electrode gel mixture. Wherein, the first solvent includes EC and DMC, and based on the total volume of the first solvent, the volume percentage of EC is 50%, and the volume percentage of DMC is 50%. The concentration CLi1 of the first lithium salt in the first intermediate is 1 mol / L; based on the mass of the first intermediate, the mass percentage content Wp1 of the first polymer is 15%. Based on the mass of the negative electrode gel mixture, the mass percentage content w1 of the negative electrode active material is 90%, the mass percentage content w2 of the negative electrode conductive agent is 3%, and the sum of the mass percentage content w3 of the first lithium salt, the first solvent and the first polymer is 7%. The silicon carbon material is a silicon carbon composite material, and based on the mass of the silicon carbon composite material, the mass percentage content of the silicon element is 50%, and the mass percentage content of the carbon element is 50%.
[0113] (2) The negative electrode gel mixture is uniformly coated on one surface of a negative electrode current collector copper foil with a thickness of 12 μm to obtain a negative electrode sheet coated with a negative electrode material layer on one side. The surface density of the negative electrode material layer is 2.3 g / m 2 . Then, the second polymer polyvinylidene fluoride is dissolved in the second solvent, and then the second lithium salt LiPF6 is added and mixed evenly to obtain a first gel electrolyte. The first gel electrolyte is coated on the surface of the negative electrode material layer to form a first gel electrolyte layer. Wherein, the second solvent includes EC and DMC. Based on the total volume of the second solvent, the volume percentage of EC is 50%, and the volume percentage of DMC is 50%; the concentration CLi2 of the second lithium salt in the first gel electrolyte is 1 mol / L; based on the mass of the first gel electrolyte layer, the mass percentage of the second polymer Wp2 is 15%; the viscosity η1 of the first gel electrolyte is 100000 mPa·s; the surface density CW1 of the first gel electrolyte layer is 20 g / m 2 ; The thickness H1 of the first gel electrolyte layer is 10 μm; The ionic conductivity σ of the first gel electrolyte layer is 8 mS / cm. Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer and a first gel electrolyte layer coated on both sides in sequence. Then, after cutting and slitting, a negative electrode sheet with a specification of 51 mm × 44.2 mm is obtained.
[0114] (3) Under the conditions of ambient temperature of 25°C and humidity of 1.0%, the lithium foil was rolled into a copper foil support layer with a thickness of 14 μm to form a lithium supplement layer, and the roller pressure P12 was 1.5T / 10mm to obtain a lithium supplement layer / support layer composite structure. The thickness H2 of the lithium supplement layer was 0.03mm; along the running direction of the lithium supplement layer, the tensile strength K1 of the lithium supplement layer (including the support layer) was 72N / 10mm.
[0115] (4) Under the condition of an ambient temperature of 25° C. and a humidity of 1.0%, the lithium supplement layer obtained in step (3) and the first gel electrolyte layer obtained in step (2) are laminated by pressing into a sheet, and a pre-lithiation treatment is performed. The lamination pressure P2 of the lithium supplement layer and the first gel electrolyte layer is 0.3 MPa, the lamination time t2 of the lithium supplement layer and the first gel electrolyte layer is 0.5 h, and the lamination temperature T2 of the lithium supplement layer and the first gel electrolyte layer is 45° C. After the pre-lithiation treatment is completed, the lithium supplement layer and the first gel electrolyte layer are peeled off to form a pre-lithiation negative electrode sheet.
[0116] In the pre-lithiated negative electrode sheet, based on the mass of the negative electrode material layer, the mass percentage W1 of the negative electrode active material is 83.47%, the mass percentage W2 of the negative electrode conductive agent is 2.78%, and the sum of the mass percentages W3 of the first lithium salt, the first solvent and the first polymer is 6.49%.
[0117] <Preparation of Secondary Battery>
[0118] (1) The third lithium salt LiPF6, the third solvent, and the third polymer polyvinylidene fluoride are mixed evenly to obtain a second intermediate, and then the positive electrode active material lithium cobalt oxide (LiCoO2) and the positive electrode conductive agent acetylene black are added and mixed evenly to obtain a positive electrode gel mixture. Among them, the third solvent includes EC and DMC. Based on the total volume of the third solvent, the volume percentage of EC is 50%, and the volume percentage of DMC is 50%. The concentration CLi3 of the third lithium salt in the second intermediate is 1 mol / L; based on the mass of the second intermediate, the mass percentage of the third polymer Wp3 is 15%. The positive electrode gel mixture is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12 μm to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Among them, the surface density of the positive electrode material layer is 4.6 g / m 2 . Then repeat the above steps on the other surface of the aluminum foil to obtain a gel-state positive electrode sheet coated with a positive electrode material layer on both sides. Then, after cutting and slitting, a gel-state positive electrode sheet with a specification of 48mm×41.2mm is obtained. Among them, based on the mass of the positive electrode material layer, the mass percentage content W4 of the positive electrode active material is 90%, the mass percentage content W5 of the positive electrode conductive agent is 3%, and the sum of the mass percentage content W6 of the third lithium salt, the third solvent and the third polymer is 7%.
[0119] (2) The fourth polymer polyvinylidene fluoride is dissolved in the fourth solvent, and then the fourth lithium salt LiPF6 is added and mixed evenly to obtain a second gel electrolyte. The second gel electrolyte is coated on one surface of a porous polypropylene film (provided by Celgard) with a thickness of 5 μm to form a second gel electrolyte layer. The fourth solvent includes EC and DMC, based on the total volume of the fourth solvent, the volume percentage of EC is 50%, and the volume percentage of DMC is 50%; the concentration of the fourth lithium salt in the second gel electrolyte CLi4 is 1 mol / L; based on the mass of the second gel electrolyte layer, the mass percentage of the fourth polymer Wp4 is 15%; the viscosity η2 of the second gel electrolyte is 100000 mPa·s; the surface density CW2 of the second gel electrolyte layer is 20 g / m 2 ; The thickness H4 of the second gel electrolyte layer is 10 μm.
[0120] (3) The gel-state positive electrode plate, the gel-state separator and the pre-lithiated negative electrode plate are stacked in order, wherein the second gel-state electrolyte layer is arranged opposite to the gel-state positive electrode plate, and then the electrode assembly is wound to obtain the electrode assembly. After the electrode lugs are welded, the electrode assembly is placed in an aluminum-plastic film, and the secondary battery is obtained through vacuum packaging, standing, formation (charging to 3.5V at a constant current of 0.02C, and then charging to 3.9V at a constant current of 0.1C), degassing, trimming, and capacity treatment.
[0121] Example 1-2 to Example 1-20
[0122] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0123] Example 2-1 to Example 2-8
[0124] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1.
[0125] Example 2-9 to Example 2-14
[0126] Except that the coating amount of the first gel electrolyte was adjusted so that the surface density of the first gel electrolyte layer was as shown in Table 2, the rest was the same as Example 1-1.
[0127] Example 3-1 to Example 3-2
[0128] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1.
[0129] Example 4-1 to Example 4-11
[0130] Except for adjusting the relevant preparation parameters according to Table 4, the rest is the same as Example 1-1.
[0131] Example 5-1 to Example 5-4
[0132] Except for adjusting the relevant preparation parameters according to Table 5, the rest is the same as Example 1-1.
[0133] Example 5-5 to Example 5-6
[0134] The method was the same as Example 1-1 except that the coating amount of the second gel electrolyte was adjusted so that the surface density of the second gel electrolyte layer was as shown in Table 5.
[0135] Example 6-1 to Example 6-2
[0136] Except for adjusting the relevant preparation parameters according to Table 6, the rest is the same as Example 1-1.
[0137] Comparative Example 1-1 to Comparative Example 1-5
[0138] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0139] The preparation parameters and electrical performance parameters of each embodiment and comparative example are shown in Tables 1 to 6.
[0140]
[0141]
[0142] From Examples 1-1 to 1-20 and Comparative Examples 1-1 to 1-5, it can be seen that the lithium replenishment method provided in the present application is used to prepare a pre-lithiated negative electrode plate, and the obtained pre-lithiated negative electrode plate is applied to a secondary battery, and the prepared secondary battery has a high lithium replenishment amount, first coulomb efficiency, cycle capacity retention rate and energy density, indicating that the first coulomb efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved. In Comparative Examples 1-1 to 1-5, the lithium replenishment method is not within the scope of the present application, and the prepared secondary battery has a low lithium replenishment amount, first coulomb efficiency, cycle capacity retention rate and energy density.
[0143] The types of the first lithium salt and the second lithium salt usually affect the first coulombic efficiency, cycle capacity retention rate and energy density of the secondary battery. It can be seen from Examples 1-1, 1-9 to 1-12 that the types of the first lithium salt and the second lithium salt are within the scope of this application, and the prepared secondary battery has a higher lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved.
[0144] It can be seen from Example 1-1, Example 1-13, and Example 1-14 that as the roller pressure P12 increases, the first coulombic efficiency, cycle capacity retention rate, and energy density of the secondary battery first remain unchanged and then decrease. This is because as the roller pressure P12 increases, the thickness of the lithium replenishment layer gradually decreases, and the amount of lithium replenishment provided by the lithium replenishment layer gradually decreases. The amount of lithium replenishment in Example 1-1 and Example 1-13 both meets the consumption, and the first coulombic efficiency, cycle capacity retention rate, and energy density of the secondary battery are close; while the amount of lithium replenishment in Example 1-14 is less, so the first coulombic efficiency, cycle capacity retention rate, and energy density of the secondary battery are lower.
[0145] Table 2
[0146]
[0147] The concentration of the second lithium salt in the first gel electrolyte usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of the secondary battery. It can be seen from Examples 1-1, 2-1 to 2-4 that the concentration of the second lithium salt in the first gel electrolyte is within the range of this application, and the prepared secondary battery has a higher lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved.
[0148] The mass percentage of the second polymer usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of the secondary battery. It can be seen from Examples 1-1, 2-5 to 2-8 that the mass percentage of the second polymer is within the scope of this application, and the prepared secondary battery has a higher lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved.
[0149] The ionic conductivity of the first gel electrolyte layer usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of the secondary battery. It can be seen from Examples 1-1, 2-1 to 2-8 that the ionic conductivity of the first gel electrolyte layer is within the scope of this application, and the prepared secondary battery has a high lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved.
[0150] The surface density of the first gel electrolyte layer usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of the secondary battery. It can be seen from Example 1-1, Example 2-9 to Example 2-14 that the surface density of the first gel electrolyte layer is within the scope of this application, and the prepared secondary battery has a higher lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that it can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. In Example 1-1, Example 2-9 to Example 2-14, the smaller the surface density of the first gel electrolyte layer, the shorter the lithium ion transmission distance, and under the same lithium supplement conditions, the greater the amount of lithium supplement, the higher the first coulombic efficiency and energy density of the secondary battery, but too much lithium supplement will affect the cycle performance of the secondary battery.
[0151] Table 3
[0152]
[0153] The sum of the mass percentages of the negative electrode active material, the negative electrode conductive agent, the first lithium salt, the first solvent and the first polymer usually affects the first coulombic efficiency, the cycle capacity retention rate and the energy density of the secondary battery. It can be seen from Example 1-1, Example 3-1 to Example 3-2 that the sum of the mass percentages of the negative electrode active material, the negative electrode conductive agent, the first lithium salt, the first solvent and the first polymer is within the scope of this application, and the prepared secondary battery has a higher lithium replenishment amount, the first coulombic efficiency, the cycle capacity retention rate and the energy density, indicating that it can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. In Example 3-1, the mass percentage of the negative electrode active material is low, the lithium replenishment kinetics is relatively poor, and the lithium replenishment amount is relatively low; the surface density of the negative electrode material layer remains unchanged, the content of the negative electrode active material is reduced, the N / P value (the ratio of the negative electrode capacity to the positive electrode capacity, Cell balance) is reduced, and the first coulombic efficiency of the secondary battery is improved.
[0154] Table 4
[0155]
[0156]
[0157] It can be seen from Example 1-1 and Example 4-1 to Example 4-11 that the secondary battery prepared by the preparation method provided in the present application has a high lithium replenishment amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved.
[0158] The types of the third lithium salt and the fourth lithium salt usually affect the first coulombic efficiency, cycle capacity retention rate and energy density of the secondary battery. It can be seen from Examples 1-1, 4-8 to 4-11 that the types of the third lithium salt and the fourth lithium salt are within the scope of this application, and the prepared secondary battery has a higher lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved.
[0159] Table 5
[0160]
[0161]
[0162] The concentration of the fourth lithium salt in the second gel electrolyte usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of the secondary battery. It can be seen from Example 1-1, Example 5-1 to Example 5-2 that the concentration of the fourth lithium salt in the second gel electrolyte is within the range of this application, and the prepared secondary battery has a higher lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved.
[0163] The mass percentage of the fourth polymer usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of the secondary battery. It can be seen from Example 1-1, Example 5-3 to Example 5-4 that the mass percentage of the fourth polymer is within the scope of this application, and the prepared secondary battery has a higher lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved.
[0164] The surface density of the second gel electrolyte layer usually affects the first coulombic efficiency, cycle capacity retention rate and energy density of the secondary battery. It can be seen from Example 1-1, Example 5-5 to Example 5-6 that the surface density of the second gel electrolyte layer is within the scope of this application, and the prepared secondary battery has a higher lithium supplement amount, first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the secondary battery can be improved.
[0165] Table 6
[0166]
[0167] The sum of the mass percentages of the positive electrode active material, the positive electrode conductive agent, the third lithium salt, the third solvent and the third polymer usually affects the first coulombic efficiency, the cycle capacity retention rate and the energy density of the secondary battery. It can be seen from Example 1-1, Example 6-1 to Example 6-2 that the sum of the mass percentages of the positive electrode active material, the positive electrode conductive agent, the third lithium salt, the third solvent and the third polymer is within the scope of this application, and the prepared secondary battery has a higher lithium replenishment amount, the first coulombic efficiency, the cycle capacity retention rate and the energy density, indicating that it can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. Compared with Example 1-1, Example 6-1 has a reduced mass percentage of the positive electrode active material, and the surface density of the positive electrode material layer remains unchanged, which has no effect on the lithium replenishment amount of the secondary battery, but the N / P value increases, the first coulombic efficiency of the secondary battery decreases, and the energy density decreases; the positive electrode kinetics deteriorates, and the cycle capacity retention rate of the secondary battery decreases. Compared with Example 1-1, Example 6-2 has an increased mass percentage of the positive electrode active material, and the surface density of the positive electrode material layer remains unchanged, which has no effect on the amount of lithium replenishment of the secondary battery, but the N / P value decreases, and the first coulombic efficiency and energy density of the secondary battery increase; however, the bonding performance of the positive electrode material layer deteriorates, and the cycle capacity retention rate of the secondary battery decreases.
[0168] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0169] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0170] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A lithium supplementation method, comprising the following steps: (1) mixing a first lithium salt, a first solvent, a first polymer, a negative electrode active material, and a negative electrode conductive agent to obtain a negative electrode gel mixture; (2) coating the negative electrode gel mixture on at least one surface of a negative electrode current collector to form a negative electrode material layer to obtain a negative electrode sheet; (3) mixing a second lithium salt, a second solvent, and a second polymer to obtain a first gel electrolyte; applying the first gel electrolyte to the surface of the negative electrode material layer to form a first gel electrolyte layer; (4) coating a lithium metal powder slurry on the support layer, drying it, and rolling it to form a lithium supplement layer; or rolling a lithium foil and / or a lithium alloy foil onto the support layer to form a lithium supplement layer; or coating a lithium or lithium alloy molten slurry on the support layer, cooling it, and rolling it to form a lithium supplement layer; wherein the rolling pressure P1 is 0.1T / 10mm to 2T / 10mm; (5) laminating the lithium replenishing layer obtained in step (4) and the first gel electrolyte layer obtained in step (3) to perform a pre-lithiation treatment, wherein the laminating pressure P2 of the lithium replenishing layer and the first gel electrolyte layer is 0.1 MPa to 0.6 MPa, the laminating time t2 of the lithium replenishing layer and the first gel electrolyte layer is 0.01 h to 1 h, and the laminating temperature T2 of the lithium replenishing layer and the first gel electrolyte layer is 25° C. to 90° C. After the pre-lithiation treatment is completed, the lithium replenishing layer and the first gel electrolyte layer are peeled off to form a pre-lithiation negative electrode sheet; Wherein, the first solvent and the second solvent are each independently selected from at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, N,N-dimethylformamide, N-methylpyrrolidone, dioxolane, 1-butyl-3-methylimidazolium bromide or ethylene glycol dimethyl ether; The first polymer and the second polymer are each independently selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, and polyethylene glycol dimethacrylate.
2. The lithium supplementation method according to claim 1, wherein: The first lithium salt and the second lithium salt are each independently selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate) or lithium oxalatodifluoroborate.
3. The lithium supplementation method according to claim 1, wherein: The concentration CLi2 of the second lithium salt in the first gel electrolyte is 0.2 mol / L to 2 mol / L; based on the mass of the first gel electrolyte layer, the mass percentage content Wp2 of the second polymer is 1% to 30%.
4. The lithium supplementation method according to claim 1, wherein: The viscosity η1 of the first gel electrolyte is 30000 mPa·s to 200000 mPa·s.
5. A pre-lithiated negative electrode sheet prepared by the lithium replenishment method according to any one of claims 1 to 4, comprising the negative electrode current collector, the negative electrode material layer and the first gel electrolyte layer, the negative electrode material layer is arranged between the negative electrode current collector and the first gel electrolyte layer, the negative electrode material layer comprises the negative electrode active material, the negative electrode conductive agent, the first lithium salt, the first solvent and the first polymer, and the first gel electrolyte layer comprises the second lithium salt, the second solvent and the second polymer.
6. The pre-lithiated negative electrode sheet according to claim 5, wherein: The ion conductivity σ of the first gel electrolyte layer is 0.1 mS / cm to 15 mS / cm.
7. The pre-lithiated negative electrode sheet according to claim 5, wherein: The surface density CW1 of the first gel electrolyte layer is 1 g / m 2 Up to 100g / m 2 .
8. The pre-lithiated negative electrode sheet according to claim 7, wherein: The surface density CW1 of the first gel electrolyte layer is 5 g / m 2 Up to 50g / m 2 .
9. The pre-lithiated negative electrode sheet according to claim 5, wherein: Based on the mass of the negative electrode material layer, the mass percentage W1 of the negative electrode active material is 69% to 99%, the mass percentage W2 of the negative electrode conductor is 0.18% to 5.0%, and the sum of the mass percentages W3 of the first lithium salt, the first solvent and the first polymer is 0.7% to 15%.
10. A method for preparing a secondary battery, comprising the following steps: (1) mixing a third lithium salt, a third solvent, a third polymer, a positive electrode active material, and a positive electrode conductive agent to obtain a positive electrode gel mixture; applying the positive electrode gel mixture to at least one surface of a positive electrode current collector to form a positive electrode material layer to obtain a gel positive electrode sheet; (2) mixing a fourth lithium salt, a fourth solvent, and a fourth polymer to obtain a second gel electrolyte; applying the second gel electrolyte to one surface of the separator to form a second gel electrolyte layer to obtain a gel separator; (3) The gel-state positive electrode sheet, the gel-state separator and the pre-lithiated negative electrode sheet according to any one of claims 5 to 9 are stacked in sequence, and the second gel-state electrolyte layer is arranged opposite to the gel-state positive electrode sheet to obtain a secondary battery; Wherein, the third solvent and the fourth solvent are each independently selected from at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, N,N-dimethylformamide, N-methylpyrrolidone, dioxolane, 1-butyl-3-methylimidazolium bromide or ethylene glycol dimethyl ether; The third polymer and the fourth polymer are each independently selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, and polyethylene glycol dimethacrylate.
11. The preparation method according to claim 10, which satisfies at least one of the following characteristics: (1) the third lithium salt and the fourth lithium salt are each independently selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate) or lithium oxalatodifluoroborate; (2) Based on the mass of the positive electrode material layer, the mass percentage W4 of the positive electrode active material is 85% to 99%, the mass percentage W5 of the positive electrode conductive agent is 0.5% to 5%, and the sum of the mass percentages W6 of the third lithium salt, the third solvent and the third polymer is 0.5% to 10%; (3) the concentration of the fourth lithium salt in the second gel electrolyte is CLi4 from 0.2 mol / L to 2 mol / L; based on the mass of the second gel electrolyte layer, the mass percentage of the fourth polymer Wp4 is from 1% to 30%; (4) The viscosity η2 of the second gel electrolyte is 30000 mPa·s to 200000 mPa·s; (5) The surface density CW2 of the second gel electrolyte layer is 1 g / m 2 Up to 100g / m 2 .
12. A secondary battery, wherein: The secondary battery is prepared by the preparation method according to claim 10 or 11. 13 . An electronic device comprising the secondary battery according to claim 12 .
Citation Information
Patent Citations
Negative plate and lithium supplementing method using same
CN114975858A
Lithium compound, lithium nickel complex oxide precursor mixture, and method for producing lithium nickel complex oxide
JP2019043843A
Method and computer program for lockimg and unlocking of smartphone using user's location information
KR1020210000560A
Anode pre-lithiation-pre-sodiation method, pre-lithiated and pre-sodiated anode, and lithium secondary battery comprising same
US20220293910A1